2014
DOI: 10.7314/apjcp.2014.15.5.1919
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Breast Cancer in a Low Middle Income Country: Predictors in a Rural Area of Kerala, India

Abstract: Background: In India, breast cancer is the leading malignancy among women in a majority of the cancer registries. Therefore it is important to understand screening practices and its predictors, including in rural areas with high female literacy and good health indices. Materials and Methods: A cross-sectional study with multistage sampling was conducted in Vypin Block, Ernakulam district, Kerala, India. Four Panchayats (self administration units) were randomly chosen and a woman in every second household was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 30 publications
(38 reference statements)
9
28
1
Order By: Relevance
“…The findings indicated that the level of awareness of BC is sub-optimal among the women participants of Delhi. Our overall results are consistent with studies done in other parts of the India (Somdatta and Baridalyne, 2008;Gupta, 2009;Khokhar, 2009;Yadav and Jaroli, 2010;Shalini et al, 2011;Grosse et al, 2013;Parameshwari et al, 2013;Sathian et al, 2014;Sreedevi et al, 2014) and world (Okobia et al, 2006;Elsie et al, 2010;Forbes et al, 2011;Samganje and Mafuvadze, 2012;Radi, 2013;Karadag et al, 2014;Kratzke et al, 2014;Asif et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings indicated that the level of awareness of BC is sub-optimal among the women participants of Delhi. Our overall results are consistent with studies done in other parts of the India (Somdatta and Baridalyne, 2008;Gupta, 2009;Khokhar, 2009;Yadav and Jaroli, 2010;Shalini et al, 2011;Grosse et al, 2013;Parameshwari et al, 2013;Sathian et al, 2014;Sreedevi et al, 2014) and world (Okobia et al, 2006;Elsie et al, 2010;Forbes et al, 2011;Samganje and Mafuvadze, 2012;Radi, 2013;Karadag et al, 2014;Kratzke et al, 2014;Asif et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…It's evident from different studies done on BC awareness (Gupta, 2009;Al-Naggar et al, 2011;Rasu et al, 2011;Kanaga et al, 2011;Khokher et al, 2011;Kumar et al, 2011;Grosse et al, 2013;Karadag et al, 2014;Sreedevi et al, 2014) that there has been positive association between BC awareness and educational status, including the present study. Grosse et al (2013) has emphasised that education programmes, aiming to increase BC awareness should target less educated women to increase their knowledge about BC.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Limitation of this study were did not examine the survival rates and mortality rates according to disease stage Therefore, early diagnosis of the breast cancer by different approaches at early stages of disease and finding cancer before lymph node involvement can lead to a considerable reduction in mortality for women. Imparting a high quality breast cancer awareness and early diagnosis initiative at this juncture can help to consolidate the gains and also tackle knowledge, resource and psychosocial barriers (Sreedevi et al, 2014). Najafi et al showed that the mortality rate will be reduced by using screening mammography and useful adjuvant therapy.…”
mentioning
confidence: 99%
“…As mentioned earlier, there is dearth of mass screening programs, for example, efforts for breast cancer screening using methods such as mammography is very low with <2% coverage of the female population. [8,9] According to an assessment conducted by ICMR in association with the WHO in 2006, mass screening for human papillomavirus using Papanicolaou (PAP) smear method lacks feasibility due to high cost (www.icmr.nic.in/Publications/ plan/ICMR XII th Plan (2012-2017).pdf). Consequently, due to limited focus and allocation of public resources, less than 2% of female population can be covered with the current facilities available for PAP smear screening.…”
mentioning
confidence: 99%